CFTR bearing variant p.Phe312del exhibits function inconsistent with phenotype and negligible response to ivacaftor - Karen S. Raraigh; Kathleen C. Paul; Jennifer L. Goralski; Erin N. Worthington; Anna V. Faino; Stanley Sciortino; Yiting Wang; Melis A. Aksit; Hua Ling; Derek L. Osorio; Frankline M. Onchiri; Shivani U. Patel; et al. (JCI Insight, 2022)
The chloride channel dysfunction caused by deleterious cystic fibrosis transmembrane conductance regulator (CFTR) variants generally correlates with severity of cystic fibrosis (CF). However, 3 adults bearing the common severe variant p.Phe508del (legacy: F508del) and a deletion variant in an ivacaftor binding region of CFTR (p.Phe312del; legacy: F312del) manifested only elevated sweat chloride concentration (sw[Cl–]; 87–105 mEq/L). A database review of 25 individuals with F312del and a CF-causing variant revealed elevated sw[Cl–] (75–123 mEq/L) and variable CF features. F312del occurs at a higher-than-expected frequency in the general population, confirming that individuals with F312del and a CF-causing variant do not consistently develop overt CF features. In primary nasal cells, CFTR bearing F312del and F508del generated substantial chloride transport (66.0% ± 4.5% of WT-CFTR) but did not respond to ivacaftor. Single-channel analysis demonstrated that F312del did not affect current flow through CFTR, minimally altered gating, and ablated the ivacaftor response. When expressed stably in CF bronchial epithelial (CFBE41o–) cells, F312del-CFTR demonstrated residual function (50.9% ± 3.3% WT-CFTR) and a subtle decrease in forskolin response compared with WT-CFTR. F312del provides an exception to the established correlation between CFTR chloride transport and CF phenotype and informs our molecular understanding of ivacaftor response.